IMPROVEMENT OF JAVANESE SCRIPT WRITING SKILL THROUGH THE COOPERATIVE LEARNING MODEL OF FLANNELGRAPH MEDIA-AIDED THINK TALK WRITE (TTW) TYPE - Winda Dwi Astuti; Soegiyanto Soegiyanto; Sukarno Sukarno (Universitas Sebelas Maret, 2018)
The objective of this research is to improve the Javanese script writing skill through the application of the Cooperative Learning Model of Flannelgraph media-aided Think Talk Write (TTW) type of the students in Grade IVA of State Primary School 03 of Karanganyar in Academic Year 2017/2018. This research used the classroom action research with two cycles. Each cycle consisted of four phases, namely: planning, implementation, observation, and reflection. Its subjects were the students as many as 34. The data were collected through test, observation, in-depth interview, and documentation. They were validated by using the content validity, and data source and data collection technique triangulations. The data were then analyzed by using the interactive analysis and the descriptive comparative analysis.The result of this research shows the improvement from pre-cycle, cycle I until cycle II. Following the treatments, the students’ learning completeness was 82,35% in cycle II.